2020
DOI: 10.1016/j.ymthe.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of M2-Deviated Microglia Promotes Recovery of Motor Function after Spinal Cord Injury in Mice

Abstract: Despite the poor prognosis of spinal cord injury (SCI), effective treatments are lacking. Diverse factors regulate SCI prognosis. In this regard, microglia play crucial roles depending on their phenotype. The M1 phenotype exacerbates neuroinflammation, whereas the M2 phenotype promotes tissue repair and provides anti-inflammatory effects. Therefore, we compared the effects of M2 and M1 microglia transplantation on SCI. First, we established a method for effective induction of M1 or M2 microglia by exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 69 publications
3
97
0
Order By: Relevance
“…Finding therapeutic modalities that ameliorate autophagic reduction, or ones that can be targeted away from neurons, is crucial. In conditions of trauma such as spinal cord injury that are accompanied by elevated ATP and autophagic dysregulation (Galluzzi et al, 2016 ; Li et al, 2019 ), the modulation of microglial activation state has been proposed to enhance repair (Hu et al, 2015 ; Akhmetzyanova et al, 2019 ; Kobashi et al, 2020 ). However, treatment timing is critical, as transient P2X 7 receptor stimulation may enhance autophagy and promote M2a microglia, while sustained stimulation can inhibit autophagy and promote proinflammatory M1 microglia (Fabbrizio et al, 2017 ; Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finding therapeutic modalities that ameliorate autophagic reduction, or ones that can be targeted away from neurons, is crucial. In conditions of trauma such as spinal cord injury that are accompanied by elevated ATP and autophagic dysregulation (Galluzzi et al, 2016 ; Li et al, 2019 ), the modulation of microglial activation state has been proposed to enhance repair (Hu et al, 2015 ; Akhmetzyanova et al, 2019 ; Kobashi et al, 2020 ). However, treatment timing is critical, as transient P2X 7 receptor stimulation may enhance autophagy and promote M2a microglia, while sustained stimulation can inhibit autophagy and promote proinflammatory M1 microglia (Fabbrizio et al, 2017 ; Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages could antagonize and inhibit the inflammation caused by inflammatory molecules related to M1 macrophages [10][11][12]. Previous studies have reported that M2 microglia can promote recovery of motor function after spinal cord injury in mice and delay the progression of EAE [13,14]. Macrophages are homologous to microglia and are easier to obtain and culture.…”
Section: Introductionmentioning
confidence: 99%
“…This might be attributed to the increase in adenosine during conditions of increased metabolic demand or pathological states such as ischemia, pain and inflammation [ 49 ]. When necessary, ATP is increased and induces the A3R accumulation at the leading edge of immunocytes [ 50 ]. The increase in A3R and adenosine may be considered as an endogenous protective mechanism.…”
Section: Discussionmentioning
confidence: 99%